Combination of marine bioactive compounds and extracts for the prevention and treatment of chronic diseases - Ebrahimi, Belgheis; Baroutian, Saeid; Li, Jinyao; Zhang, Baohong; Ying, Tianlei; Lu, Jun (Frontiers in Nutrition, 2023)
Background In recent years, marine-based functional foods and combination therapy are receiving greater recognition for their roles in healthy lifestyle applications and are being investigated as viable and effective strategies for disease treatment or prevention. Aim of the review This review article presents and discusses the relevant scientific publications that have studied the synergistic and additive effects of natural marine bioactive compounds and extract combinations with anti-obesity, anti-inflammatory, antioxidant, and chemopreventive activities in the last two decades. The paper presents the mechanism of action and health benefits of developed combinations and discusses the limitation of the studies. Furthermore, it recommends alternatives and directions for future studies. Finally, it highlights the factors for developing novel combinations of marine bioactive compounds. Key scientific concepts of review Combination of marine bioactive compounds or extracts affords synergistic or additive effects by multiple means, such as multi-target effects, enhancing the bioavailability, boosting the bioactivity, and neutralizing adverse effects of compounds in the mixture. For the development of marine-based combinations, there are key points for consideration and issues to address: knowledge of the mechanism of action of individual compounds and their combinations, optimum ratio and dosing of compounds, and experimental models must all be taken into account. Strategies to increase the number and diversity of marine combinations, and further development of marine-based functional foods, are available. However, only a small number of natural marine bioactive combinations have been assessed, and most research has been focused on fish oil and carotenoid synergy. Therefore, more research and resources should be spent on developing novel marine bioactive combinations as functional foods and nutraceuticals.